The Influence of Light Quality on the Growth and Productivity of Cannabis sativa - Dlaymi, Shaalin (Université d'Ottawa | University of Ottawa, 2026)
The Cannabis industry in Canada has grown into a 3.2-billion-dollar industry since legalization in 2018. Cannabis sativa (cannabis) is used for both medical and recreational purposes and is commonly cultivated indoors under light emitting diode (LED) lighting systems. Light is one of the most influential environmental parameters mediating plant growth, development, and secondary metabolite profiles. The objective of this study is to investigate the growth, productivity and yield of Cannabis sativa under different LED lighting treatments. We examine these effects by utilizing full-spectrum light enriched in red, blue, and far-red wavelengths in different combinations for a total of 12 weeks. Data on growth, morphology, physiology, and chemical profiles was collected at different timepoints during the experiment. These data will provide important insight into how different light qualities can affect cannabis productivity and biology. This knowledge will enable growers to optimize lighting regimes during commercial cultivation practices.
Keywords: Cannabis sativa; Light quality; Photosynthesis; Photomorphogenesis; Photosynthesis; Cannabinoids